DIPLOMASI EKONOMI PEMERINTAH INDONESIA DALAM MENINGKATKAN EKSPOR TEH KE AMERIKA SERIKAT PERIODE 2008 - 2018 - Fitri Indriani, (2022)
Tea commodities are one of the leading plantation commodities in Indonesia. This is an opportunity for Indonesia to market tea commodities in the global market. Indonesian tea itself reached its peak in the United States market in 2007. Unfortunately, the quantity of Indonesian tea exports to the United States continued to decline in the following years. This is compounded by falling tea prices, rising tea stocks in the world, the emergence of competing countries, and also the Food Safety Modernization Act (FSMA) policy created by the FDA makes the bureaucracy of the entry of Indonesian tea commodities into the United States more complicated. In this case, the Indonesian government must conduct economic diplomacy in order to increase Indonesia's tea exports which decreased in the period 2008 - 2018. This research uses qualitative descriptive methods with economic diplomacy theory to analyze existing factors and problems, and explain how the Indonesian government's efforts in resolving the decline in tea exports in the period 2008 - 2018.